Genetic evidence for replication enhancement from a distance. - Gennaro, M L (1993)
Rolling circle replication of the Staphylococcus aureus plasmid pT181 requires interaction of the RepC initiator protein with the origin of replication (the ori site). A second site named cmp, which is distant from ori, is thought to stimulate replication, since a mutant pT181 plasmid lacking cmp cannot coexist with a cmp+ wild-type plasmid. Second-site mutations compensating for the loss of cmp were shown to map in repC. The compensatory mutations produced RepC proteins that, unlike the wild-type, either failed to discriminate between cmp+ and cmp- plasmids or preferred cmp- to cmp+ plasmids. These studies demonstrate that cmp stimulates the interaction of the replication initiator protein with the origin and therefore enhances DNA replication from a distance.